In the line of fire : how to handle tough questions when it counts - Weissman, Jerry (Pearson Prentice Hall, 2005)
"Jerry Weissman has made a career of preparing senior executives for that moment. He's coached nearly 500 CEOs for their IPO road shows, the most critical presentations of their careers. Now, he's written an indispensable guide to answering the toughest questions you'll ever face." "Using compelling examples from presidential debates to financial investor meetings, Weissman shows you how to respond with perfect assurance. You'll discover how to avoid the defensive, evasive, or contentious answers that have destroyed careers and can ruin your credibility. You'll learn how to control your entire exchange with a hostile questioner: the question, the answer, the questioner, the audience, the timing, and above all, yourself."--Jacket.